2021
DOI: 10.3389/fnana.2021.669631
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Characterization of Schizophrenia-Associated Gene Zswim6 in Mouse Forebrain

Abstract: Schizophrenia is a devastating neuropsychiatric disease with a globally 1% life-long prevalence. Clinical studies have linked Zswim6 mutations to developmental and neurological diseases, including schizophrenia. Zswim6’s function remains largely unknown. Given the involvement of Zswim6 in schizophrenia and schizophrenia as a neurodevelopmental disease, it is important to understand the spatiotemporal expression pattern of Zswim6 in the developing brain. Here, we performed a comprehensive analysis of the spatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Furthermore, we found a EUR-specific adaptive haplotype spanning 213.9 kb at ZSWIM6 ( Figures 2 B and S17 B). Knockout mouse studies have shown that ZSWIM6 was expressed in the key brain regions involved in the pathogenesis of schizophrenia, 63 and it might regulate the morphology of striatal neurons and motor function. 64 The adaptive haplotype was carried by 43.9% of the EUR individuals but was very rare in EAS individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we found a EUR-specific adaptive haplotype spanning 213.9 kb at ZSWIM6 ( Figures 2 B and S17 B). Knockout mouse studies have shown that ZSWIM6 was expressed in the key brain regions involved in the pathogenesis of schizophrenia, 63 and it might regulate the morphology of striatal neurons and motor function. 64 The adaptive haplotype was carried by 43.9% of the EUR individuals but was very rare in EAS individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription factor encoded by the ZSWIM6 gene is synthesized in the brain and can affect the expression of a number of genes. Mutations in this gene lead to malformations of the brain [91][92][93]. Figure 11 shows the binding schemes of piR-3215034 and piR-6885965 to the mRNA of the ZSWIM6 gene.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several studies have linked ZSWIM4/5/6 with vertebrate neurogenesis and forebrain development. For instance, in the mouse, the paralogs zswim4-6 were found to be expressed in the forebrain with distinct spatiotemporal patterns ( Chang et al, 2020 ; Chang et al, 2021 ). Zswim6 knockout mice display abnormal striatal neuron morphology and motor function ( Tischfield et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%